The seasonal hydrodynamic habitat - Imberger, J.; Marti, Clelia (2014)
© Springer Science+Business Media Dordrecht 2014. In this chapter, we present a detailed analysis of the annual thermal regime of Lake Kinneret based on high-resolution thermistor chain and meteorological data collected by the Centre for Water Research at the University of Western Australia during the period April 2007–April 2008. Five seasonal regimes of the yearly cycle are defined to illustrate the main physical aspects of the lake hydrodynamics and their effects on ecological processes.